A rapid lateral flow assay using immunomagnetic nanoparticles for detecting mango allergen residues in processed foods - Tsai, Wen‐Che; Yin, Hsin‐Yi; Lin, Ya‐Ting; Liu, Hung‐Jen; Tseng, Cheng‐Yen; Wen, Hsiao‐Wei (Journal of food safety, 2021)
This study develops a rapid lateral flow assay (LFA) that uses immunomagnetic nanoparticles (IMNPs) to detect mango major allergen (Man i1) in food products. Monoclonal antibodies (2F1 and 21A5) were prepared; mAb‐2F1 was modified on the surface of IMNPs and mAb‐21A5 was immobilized on the test line of the LFA strips. Following optimization, the limit of detection (LOD) of this developed LFA was 6.2 ng/mL for rMan i1 with a linear range of 5–100 ng/mL. The assay also had high specificity in the analysis of nine vegetables and fruits. Furthermore, 22 food products were analyzed by this assay and mango allergens were detected in 13 food products that contained mango. In conclusion, a rapid LFA that uses IMNPs was developed herein for the detection of the major mango allergen Man i1 in processed foods. The rapid detection method of IMNP‐based LFA is developed for detecting mango major allergen (Man i1).